Workplace Spirituality and Team Spirit at Work : A Team -Level Contextualization of Spirituality - Nandan Prabhu, K. P.; Rodrigues, Lewlyn L. R.; Ramana Kumar, K. P. V. (Prabandhan: Indian Journal of Management, 2016)
The paper aimed to investigate the issue of conceptualizing workplace spirituality at the team level. In this regard, this paper has reviewed the conceptualizations of spirituality so as to connect them to the conceptualizations of workplace spirituality. The originality of this paper lies in the discussion on categories of spirituality and their relationship with the varied conceptualizations of workplace spirituality. Further, this paper has deliberated upon the issue of contextualizing workplace spirituality at the team level by discussing the construct of ’team spirit at work’. However, this paper has not discussed the theoretical underpinnings of the concept of workplace spirituality. This paper has contributed to the workplace spirituality research discourse by building a link between the dimensions of the concept of spirituality with the dimensions of the concept of workplace spirituality and the construct of team spirit at work.